(untitled) (Pulse, 2023)
During air travel, increasing hypoxia with altitude ascent is a potentially serious problem for patients with hypoxemic chronic airway obstruction (CAO). Travel by air is the most popular way of transport nowadays & estimated that each year worldwide, more than 3 billion passengers travel by air & 736 million in the United States alone. For most passengers, even those with respiratory disease, air travel is safe and comfortable. Some patients with COPD &other Chronic Lung diseases may be at risk but, with screening, these patients can be identified and most of them can travel safely with supplemental oxygen. Some patients with chronic lung disease may have mild hypoxemia at sea level but during air travel in a hypobaric hypoxic environment, compensatory pulmonary mechanisms may be inadequate despite normal sea-level oxygen requirements. In addition, compensatory cardiovascular mechanisms may be less effective in some patients who are unable to increase cardiac output. Air travel also presents an increased risk of venous thromboembolism. It’s estimated that, almost 1 medical emergency for every 600 flights. Respiratory symptoms accounted for 12% of all these in-air emergencies. Pulse Volume 12-14 2020-2022 p.16-21